The PENGEMBANGAN VLAN DENGAN VLAN TRUNKING PROTOCOL (VTP) MODE MENGGUNAKAN SWITCH CISCO DI BANK SYARIAH INDONESIA - Pirzi Kurniawan; Kussigit Santosa (CV. Multi Kreasi Media, 2022)
In the development of an enterprise network, it may require different processing (VoIP network, server, network, LAN, gateway) but still be in the same infrastructure and location.Or it could be the other way around, having several devices with different infrastructure and locations, but still in the same network segment. It becomes especially important when VLANs are used, i.e. corporate networks are becoming more and more important and broadcasting traffic is becoming a burden for the entire network. This overburden caused by Traffic Broadcast caused the network to be unresponsive and unresponsive before. VLAN is a Virtual LAN, which is a LAN network that is virtually created on a switch. A standard switch will usually move traffic from one port to all the other ports when there is traffic with the same broadcast domain passing through that port. For a particular switch, they are able to create several different LANs with different ids on each port, and will only add traffic to ports that have the same id. VLANs can divide the network into several segments with minimal cost of implementation. The use of VLAN Trunking Protocol (VTP) will make it easier for network administrators to manage VLAN.